Paradoxical Pluralism: Training Militants for Tolerance in an Indonesian Youth Movement - Lukens-Bull, Ronald Alan; Makin, Al (Studia Islamika, 2025)
This article explores the paradoxical militarized pluralism as practiced by Banser, the paramilitary wing of Ansor (Nahdlatul Ulama’s youth movement). Based on ethnographic fieldwork and reading literature about the issue, the study reveals how Banser’s ideological training programs propagate pluralistic values at the grassroots level, reinforcing Indonesia’s ideological foundation Pancasila. However, the organization’s reliance on hierarchical command structures contradicts liberal democratic ideals of reasoning and individual conscience. The paper also demonstrates Banser’s dual role as both a bulwark against religious extremism and a site of ongoing ideological contestation in national level of Indonesia and within NU’s. The finding shows a model of “illiberal pluralism” - communally bounded, effective in promoting pluralism in the grassroot level, yet it may slip into authoritarian style, merely fulfilling the political interest of its elite commands. Ultimately, the study questions whether institutionalized militant methods can produce authentic tolerance, or merely enforce a hegemonic version of top-down command. The paper invites broader debates about pluralism’s compatibility with illiberal political frameworks in post-reformasi Indonesia, while democratic trajectory is declining.